Study of electrolytes in patients of Dengue in a tertiary care hospital in India - Relwani, Prakash Ram; Redkar, Neelam N.; Garg, Deepanshu (International Journal of Advances in Medicine, 2019)
Background: Dengue is a mosquito borne viral infection. It is the most common arboviral disease globally. In the year 2017, India had 1,53,635 cases of dengue with 226 deaths. Electrolyte disturbances reported in dengue infection are hyponatremia, hypokalaemia and hyperchloremia. Considering the serious nature of effects of dyselectrolytemias and high incidence of dengue in India, it is necessary to have a thorough understanding about electrolyte disturbances in Dengue, so as to predict, diagnose and treat them accordingly. Methods: This study was performed in a tertiary care centre in Mumbai, India. The study was a prospective observational cross-sectional study. 150 Patients diagnosed with Dengue were enrolled for the study. Patients’ demographic data, clinical history, examination findings and investigations including electrolyte values were recorded and analysed. Results: A higher incidence of dengue was seen in young age group among admitted patients (74%). Hyponatremia (45.33%) and Hypokalaemia (10.60%) were more commonly observed than hypernatremia (3.33%) and hyperkalaemia (3.33%). Hypochloraemia (6.66%) was seen slightly more than hyperchloraemia (6.00%). Fever was Present in 98.66%, retro orbital headache in 86.66%, vomiting in 56.00%, joint pain in 69.00%, lethargy in 70.66%, breathlessness in 36.00%, bleeding in 8.66%, abdominal pain /tenderness in 18.00%. 85.00% had low platelet count, 30.66% had low hemoglobin and 36.66% had leucopenia. Haematocrit was found to be less in 27.33% and high in 1.33%. Conclusions: From the above results we concluded that, there is a need to have a degree of suspicion about dyselectrolytemias while managing patients with Dengue. Also, patients need to be subjected to necessary lab investigations early during management so that if abnormalities are found, they can be promptly and appropriately managed as some of these abnormalities may lead to increased severity as well as mortality.